PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR SISWA KELAS IV SDN MARGOREJO 1/403 SURABAYA - Ghaida Alsynasta Putri At Thoriq, Arif Mahya Fanny (STKIP Subang, 2025)
The point of this study is to look into how the role-playing learning model affected the schoolwork of fourth-grade students at SDN Margorejo 1/403 Surabaya who were taking a Pancasila Education class with the theme of working together. A quasi-experimental strategy with a non-equivalent control group is used in this study, which combines a quantitative approach with experimental methods. The experimental and control groups will take a pre-test before the intervention and a post-test after the intervention as part of this plan. Based on the findings of this study, fourth-grade students' learning outcomes in Pancasila Education about working together have improved significantly. This group's average score before the test was 51, and their average score after the test was 85. The experimental group also had an average pre-test score of 51, but after the role-playing learning model was used, the average post-test score went up to 88. This way of teaching really helps students learn better in Pancasila, especially when it comes to grade IV joint partnership at SDN Margorejo 1/403 Surabaya during the 2024–2025 school year.